The Influence of Waste Disposal Site on The Water and Soil Quality in Halabja Province, Kurdistan, Iraq - Mohammed, Karzan; Karim, Salar S.; Mohammed, Sherko A. (Science Journal of University of Zakho, 2018)
Solid waste disposal could be a major environmental problem in in Kurdistan region of Iraq because it is not managed properly. The main purpose of this study was to assess the influence of long term solid waste disposal on water and soil physicochemical properties. Soil and water samples were collected in and around the solid waste disposal area. The samples were analyzed for physicochemical characteristics and potentially toxic elements using ICPMS. The results revealed that some water parameters analysed well below WHO and EU standards for drinking water. Therefore, the surface and ground water samples in this study are good for drinking purposes. However, the application of water quality index (WQI) suggests that the ground and surface water around the open dumpsite are marked as good and poor water in quality respectively. High concentration of Ca in all soil samples is expected because the regional geology is calcareous. The concentrations of PTEs were found in order of Mn> Fe> Ni> Zn> Cr> Cu> Pb> Se> Cd. Although relatively high concentrations of Ni and Cr were found at all sampling points, mean concentrations of trace elements in the soil samples in the studied area were all below the soil guideline values (SGV). Enrichment factors (EFs), calculated using typical carbonate bedrock geologies, confirmed that there was typically significant enrichment in trace elements above expected background concentrations. Whereas concentrations of toxic elements were within the ‘safe’ limits in the studied agricultural areas, care should be taken because prolonged disposing of wastes in the outskirt of the city could lead to PTE accumulation in surrounding water soils.